Active fault tolerant control based on adaptive interval observer for uncertain systems with sensor faults - Wang, Xianghua; Pin Tan, Chee; Wang, Youqing; Zhang, Ziye (International journal of robust and nonlinear control, 2021)
In this article, we present an active fault tolerant control scheme based on fault detection and isolation (FDI) for a class of uncertain systems subject to sensor faults. The FDI unit consists of a fault detection (FD) module and a fault isolation (FI) module, to determine when and where the sensor fault happens. It is noted that the FD module is based on a proposed adaptive interval observer where adaptive parameters instead of conservative uncertainty bounds are used, as a result, the sensitivity to faults is improved. When the FD module detects a fault, a compensation controller (CC) and an FI module are activated. The CC is designed to maintain some level of performance assuming all sensors are faulty. After the FI module determines the location of the fault, a reconfigured controller is activated to give improved performance with reduced conservatism. Importantly, the unmeasurable states and faulty output are approximated as a linear combination of their upper and lower bounds, and linear parameter are determined by adaptive laws. Finally, a simulation example is utilized to verify the effectiveness of the proposed scheme.